Experiences and Challenges of Promoting Pro-Poor and Social Inclusion Initiatives in User Group Forestry - Paudyal, Bimala Rai; Neil, Peter; Allison, Gaia (Journal of Forest and Livelihood, 2009)
Community Forestry has tremendous potential to reduce poverty and promote social inclusion in rural communities by improving the livelihoods of the poor and excluded, in particular the livelihoods of women, dalits and disadvantaged ethnic groups. However, there exists a large gap between the potential of the programme and its achievements in reality. Addressing this gap demands strategic interventions, including a careful analysis of barriers to inclusion and the promotion of pro-poor and socially inclusive programmes and monitoring. The paper argues that Community Forestry would better contribute to poverty reduction and social inclusion if support to user groups were focused on at least three specific (and interrelated) domains of changes. These can be identified as: increasing the access of the poor and excluded to livelihood assets; strengthening the organisation, voice and agency of the poor and excluded; and advocating for the development and enforcement of pro-poor and socially inclusive policies and institutions. Key words: community forestry, social inclusion, livelihoods, gender, equity doi: 10.3126/jfl.v5i1.1979 Journal of Forest and Livelihood 5(1) February, 2006 pp.34-45